INTERNATIONAL HANDBOOK MILITARY GEOGRAPHY/EDITED BY R. MANG & H. HAUSLER - Smit, H.A.P. (Scientia Militaria - South African Journal of Military Studies, 2011)
Although the relationship between Geography and the military is long-standing and well researched, books dealing with this applied sub-discipline of geography exclusively remain rare. As such, the International handbook Military Geography is both a welcome addition to a rather sparse collection of Military Geography literature, as well as a uniquely European perspective to an otherwise American-dominated body of literature. Fifty-two contributions by authors from seven different European countries appear in this publication. The stated aim of the book is to “present selected activities and products of the military geographic community as well as important and relevant activities and products of institutions outside of this community” The authors describe the purpose of the book as “[to] show the plurality of activities and products to the [military geographic] community itself, and the armed forces in general, but also to the wider public for better understanding of what military geography deals with and what it can provide.”